ID: 97. Issue 4 (April 2016) - Abidi, M; Banerjee, A; Ledeboer, N; Hari, P
Abstract : Background: Rapidly growing nontuberculous mycobacteria can cause variety of clinical syndromes including catheter related blood stream infections (BSI). Methods: We reviewed medical records of patients with blood cultures positive for Mycobacterium mucogenicum (MM) from 2008–2013. We defined 4 at-risk groups: Stem cell transplant recipients (SCT); patients with hematologic malignancy; patients with solid tumors and other's (patient's on treatment with tumor necrotic factor inhibitors). Descriptive analysis was performed, as well as comparative analysis of neutropenic patients (absolute neutrophil count ⩽1000 /μL) with non-neutropenic patients. Results: 39 patients with MM bacteremia were identified. There were 27 SCT recipients (24 Allogeneic; 3 Autologous). 4 patients had hematologic malignancy and 4 patients had solid tumors. Others included 4 patients. At time of diagnosis, 12 were neutropenic, and 27 were non-neutropenic. No significant difference was noted in age (p=0.41) or gender (p=1.00) or rates of pure vs. mixed mycobacterial BSI (p=1.00) or more than single blood culture positivity (p=1.00) between these two groups.The predominant clinical feature was fever with mean temperature of 38 degrees C (range 37.8–40.1). There was a significant difference in presence of fever at the time of bacteremia (92% vs. 42%; p=0.005) between the neutropenic and non-neutropenic group. Central venous catheter (CVC) was present at time of bacteremia in 33 cases (P=0.15); there was no significant difference for presence of CVC between these two groups (100% vs. 78%). Median duration of antibiotic treatment was 42 days (p=0.44). All patients were treated with >1 antibiotic. Most used regimen involved clarithomycin and amikacin (n=16).While there were 15 deaths; none were attributed to MM BSI. No significant survival difference was seen at 3 years between the neutropenic and non-neutropenic group (62% vs. 56%; p=0.75). Conclusions: MM is a rare cause of CVC-associated bacteremia. In our study MM BSI was seen in immune compromised patients, predominantly in SCT recipients. BSI resolved in all patients with CVC removal and combination antimicrobial treatment. None of the patients suffered a relapse.